The Influence of Financial Attitude, Financial Technology, Locus of Control and Hedonic Lifestyle on Financial Behavior (Study on Management Study Program Students, Tribhuwana Tunggadewi University, Malang) - Reineldis Jemanis Amat; Elly Lestari; Moch Nurhidayat (IRDH International Journal of Social Sciences & Humanities, 2025)
This study aims to analyze the influence of financial attitude, financial technology, locus of control, and hedonic lifestyle on the financial behavior of students at Tribhuwana Tunggadewi University, Malang. Using a quantitative approach, this study involved 70 respondents selected through a simple random sampling method from a population of 229 students of the Management study program, class of 2021-2022. Data collection was carried out through observation, documentation, and questionnaires with a Likert scale, while data analysis used multiple regression. The results showed that financial attitude and hedonic lifestyle had a significant effect on students' financial behavior, while financial technology did not have a significant effect. Locus of control had a positive but insignificant effect on financial behavior. Overall, students with good financial attitudes, optimal use of financial technology, and good self-control tended to have more structured and planned financial behavior. However, a high hedonic lifestyle can increase the risk of ineffective financial management.